Wolves - Ohanain, Susan (Nelson Australia South Melbourne, 1994)
Wolves by Susan Ohanian is an educational children's book that provides fascinating facts about wolves, focusing on their behavior, habitat, social structures, and role in the natural world. The book dispels myths and fears surrounding wolves by highlighting their importance as intelligent, social animals that live in complex packs. Through engaging text and illustrations, Wolves helps young readers understand the vital ecological role wolves play, while also promoting respect for wildlife and the environment. It's both an informative and captivating introduction to the lives of these majestic creatures.